Community-based models for neglected tropical diseases affecting the skin: a scoping review - India Hotopf; Shahreen Chowdhury; Guillermo Robert; Mary Ellen Sellers; Maneesh Phillip; Anil Fastenau; Anil Fastenau; Anil Fastenau; Maria del Mar Marais; Constanze Vettel; Mijanur Rahman; Rajni Kant Singh; et al. (Frontiers in Tropical Diseases)
Skin neglected tropical diseases (NTDs) cause physical impairments, and socioeconomic and mental health impacts, often exacerbated by social stigma. The WHO 2030 road map calls for integrated, person-centred care; community-based groups (CBGs) present a community-led solution. However, evidence is limited and CBGs are not consistently being operationalised across health systems. The UPLIFT study is developing and piloting a harmonised CBG tool. This scoping review aimed to identify preferred practices in existing skin-NTD CBG models and recommend a holistic framework for best practice. We searched four peer-reviewed databases and key organisations’ websites, for terms related to CBGs and skin-NTDs. Eligible studies explored community models and skin NTDs and were published in English from 2000 onwards. Studies with quantitative, qualitative, or mixed method approaches, and secondary analysis or evidence synthesis were eligible. Studies failing to fulfil the criteria, opinion pieces, cross-sectional surveys, editorials, and case studies were excluded. Outcomes on key CBG domains were thematically identified and explored from literature and discussions with subject matter experts: self-care, mental health, livelihood, and governance. Data were compiled in Excel and charted according to CBG domain and other key information (e.g., outcome and method of measurement), before writing up findings thematically. Fifty-four eligible citations were identified, including 38 peer-reviewed papers. Most studies were pretest/posttests conducted in Asia, targeting mainly leprosy, with heterogeneity in study designs and evaluative measures. Only four studies explored all CBG domains, with few CBGs including formal mental health support, livelihood activities and advocacy and awareness activities. Current research on the burden of skin-NTDs is predominantly focused on leprosy, leaving a significant gap in research on other skin-NTDs, particularly in the African region. Most CBGs are failing to integrate into health systems and mainstream important programmatic components such as sustainability and gender considerations. To address these gaps and work towards a harmonised CBG approach, we present a framework of best practice and recommend further research, targeting multiple skin-NTDs in unison.